Caesarean section and risk of autism across gestational age: a multi-national cohort study of 5 million births. (24th December 2016) - Yip, Benjamin Hon Kei; Leonard, Helen; Stock, Sarah; Stoltenberg, Camilla; Francis, Richard W; Gissler, Mika; Gross, Raz; Schendel, Diana; Sandin, Sven
Abstract: Background: The positive association between caesarean section (CS) and autism spectrum disorder (ASD) may be attributed to preterm delivery. However, due to lack of statistical power, no previous study thoroughly examined this association across gestational age. Moreover, most studies did not differentiate between emergency and planned CS. Methods: Using population-based registries of four Nordic countries and Western Australia, our study population included 4 987 390 singletons surviving their first year of life, which included 671 646 CS deliveries and 31 073 ASD children. We used logistic regression to estimate odds ratios (OR) and their 95% confidence intervals (CI) for CS, adjusted for gestational age, site, maternal age and birth year. Stratified analyses were conducted by both gestational age subgroups and by week of gestation. We compared emergency versus planned CS to investigate their potential difference in the risk of ASD. Results: Compared with vaginal delivery, the overall adjusted OR for ASD in CS delivery was 1.26 (95% CI 1.22–1.30). Stratified ORs were 1.25 (1.15–1.37), 1.16 (1.09–1.23), 1.34 (1.28–1.40) and 1.17 (1.04–1.30) for subgroups of gestational weeks 26–36, 37–38, 39–41 and 42–44, respectively. CS was significantly associated with risk of ASD for each week of gestation, from week 36 to 42, consistently across study sites (OR ranged 1.16–1.38). There was no statistically significant difference between emergency and planned CS in the risk of ASD. Conclusion: Across the five countries, emergency or planned CS is consistently associated with a modest increased risk of ASD from gestational weeks 36 to 42 when compared with vaginal delivery.